ANALISIS BERPIKIR KRITIS SISWA DALAM PEMECAHAN MASALAH DITINJAU DARI KECERDASAN LOGIS MATEMATIS - Aulia, Defi Putri; Faridah, Luluk; Rohim, Abdur (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2023)
The ability of students in Indonesia in terms of critical thinking is not yet high enough. Possible solutions include giving open ended questions to students. This research aims to determine whether students with various mathematical logical intelligences can use critical thinking to solve problems. The research methodology applied is descriptive qualitative. A total of 6 students were used as study subjects who were class VII-B students at SMPN 2 Sukodadi. As a tool, a logical-mathematical intelligence questionnaire was provided which was followed by a test to see the ability to solve problems. The resulting data is in the form of test results and interview results. The research results identified that: (1) Subjects who have high mathematical logical intelligence can go through 4 stages of critical thinking, including interpretation, analysis, evaluation and inference, and are classified as TKBK 4 (very critical); (2) Subjects who have moderate mathematical logical intelligence can go through 3 stages of critical thinking including interpretation, analysis and evaluation, and are classified as TKBK 3 (critical); (3) Subjects who have low mathematical logical intelligence can only go through 1 stage of critical thinking, namely interpretation, and are classified as TKBK 1 (less critical).